Transcriptional analysis of metastatic hormone-naïve prostate cancer primary tumor biopsies reveals a relevant role for SOX11 in prostate cancer cell dissemination - Natalia Martin-Martin; Saioa Garcia-Longarte; Jon Corres-Mendizabal; Uxue Lazcano; Ianire Astobiza; Laura Bozal-Basterra; Nicolas Herranz; Hielke van Splunder; Onintza Carlevaris; Mikel Pujana-Vaquerizo; María Teresa Blasco; Ana M. Aransay; et al. (Genome Biology)
Abstract Background Metastatic hormone-naïve prostate cancer (mHNPC) is an infrequent form of this tumor type that is characterized by metastasis at the time of diagnosis and accounts for up to 50% of prostate cancer-related deaths. Despite the extensive characterization of localized and metastatic castration-resistant prostate cancer, the molecular characteristics of mHNPC remain largely unexplored. Results Here, we provide the first extensive transcriptomics characterization of primary tumor specimens from patients with mHNPC. We generate discovery and validation bulk and single-cell RNA-seq datasets and perform integrative computational analysis in combination with experimental studies. Our results provide unprecedented evidence of the distinctive transcriptional profile of mHNPC and identify stroma remodeling as a predominant feature of these tumors. Importantly, we discover a central role for the SRY-box transcription factor 11 (SOX11) in triggering a heterotypic communication that is associated with the acquisition of metastatic properties. Conclusions Our study will constitute an invaluable resource for a profound understanding of mHNPC that can influence patient management.